2021
DOI: 10.3390/nu13031005
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density, Body Composition, and Metabolic Health of Very Low Birth Weight Infants Fed in Hospital Following Current Macronutrient Recommendations during the First 3 Years of Life

Abstract: The present study longitudinally evaluated growth, bone mineral density, body composition, and metabolic health outcome in very low birth weight (VLBW) infants whose in-hospital target nutrient intake was within recent recommendations. From six months to three years, bone mineral density (dual-energy X-ray absorptiometry, DXA), body composition, and metabolic health outcome were compared with a reference group of term infants. The aim was to test whether in-hospital achieved weight gain until 36 weeks of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
7
0
3
Order By: Relevance
“…However, given the average weight gain of 21 g/kg/day in this study, the achieved average mineral accretion rate was far below fetal mineral accretion (see Section 3.2.2 .). On average, at term equivalent age and at 3 months of corrected age preterm infants still fail to achieve term infant whole-body bone mineral content (BMC) [ 28 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, given the average weight gain of 21 g/kg/day in this study, the achieved average mineral accretion rate was far below fetal mineral accretion (see Section 3.2.2 .). On average, at term equivalent age and at 3 months of corrected age preterm infants still fail to achieve term infant whole-body bone mineral content (BMC) [ 28 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear which level of mineralization must be achieved in preterm infants for prevention of long-term bone mineral deficits. Previous data have shown that there is some degree of bone mineral catch-up in VLBW infants post discharge within the first three years of life [ 32 ]. Further studies need to show which degree of reduced bone mineral content may be tolerated at discharge compared to term infants.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In der aktuellsten Longitudinaluntersuchung aus dem Jahr 2021 an 94 ehemaligen Frühgeborenen mit einem Geburtsgewicht von im Mittel ca. 1100 g und einem Gestationsalter von durchschnittlich 29 SSW wurde eine der Kontrollgruppe entsprechende Knochenmineralisation, gemessen mittels DXA-Knochendichtemessung im Alter von 3 Jahren, nicht erreicht [11]. Auch neuere Untersuchungen an Erwachsenen weisen auf eine verminderte Knochenmineralisation sowie ein erhöhtes Osteoporoserisiko hin [1].…”
Section: Folgeschädenunclassified
“…The authors concluded that the dual approach, combining M-ALP measures with the ultrasound monitoring of ossification centers favors the optimization of MBD treatments. In one important additional study [9], Mihatsch et al hypothesized that VLBW infants who were appropriate weight for their term-equivalent age (ATEA; defined by an SD weight score > −2 at 36 weeks according to Alexander growth charts, n = 39) have higher growth rates, lean body mass and fat mass, skeletal mineral deposition, and neurodevelopmental scores throughout the first three years of life than light for TEA (LTEA), defined by a weight standard deviation (SD) score of less than −2 SD at 36 weeks of gestation (n = 55). Growth, bone mineral density, body composition, and metabolic health outcome was evaluated in a prospective cohort of 94 very low birthweight infants whose in-hospital target macronutrient intake was within the recent European Society of Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) recommendations.…”
mentioning
confidence: 99%